2000
DOI: 10.1073/pnas.100076197
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of central nervous system myelination by polysialylated-neural cell adhesion molecule

Abstract: Many factors have been shown to promote myelination, but few have been shown to be inhibitory. Here, we show that polysialylated-neural cell adhesion molecule (PSA-NCAM) can negatively regulate myelin formation. During development, PSA-NCAM is first expressed on all growing fibers; then, axonal expression is downregulated and myelin deposition occurs only on PSA-NCAMnegative axons. Similarly, in cocultures of oligodendrocytes and neurons, PSA-NCAM expression on axons is initially high, but decreases as myelina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
164
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(170 citation statements)
references
References 29 publications
4
164
0
2
Order By: Relevance
“…This theory is supported by studies that implicate ECM receptors and cell-cell adhesion molecules as key mediators of mechanotransduction (23). Interestingly, adhesion molecules have previously been shown to have a role in oligodendrocyte differentiation and myelination (24)(25)(26)(27)(28). ECM receptors such as integrins are also known to modulate the effects of extrinsic growth factors on various aspects of oligodendrocyte development (29,30).…”
Section: Discussionmentioning
confidence: 51%
“…This theory is supported by studies that implicate ECM receptors and cell-cell adhesion molecules as key mediators of mechanotransduction (23). Interestingly, adhesion molecules have previously been shown to have a role in oligodendrocyte differentiation and myelination (24)(25)(26)(27)(28). ECM receptors such as integrins are also known to modulate the effects of extrinsic growth factors on various aspects of oligodendrocyte development (29,30).…”
Section: Discussionmentioning
confidence: 51%
“…This relation seems to be well conserved in mammals, since studies in mice have shown that the onset of myelination depends on down-regulation of PSA-NCAM on axonal surface, but the removal of PSA-NCAM alone was not sufficient to promote myelination in vitro (Charles et al, 2000). Accordingly, PSA-NCAM in rodents is expressed at first on all growing neuronal tracts, but myelination occurs only on axons that down-regulate PSA-NCAM (Bartsch et al, 1990;Oumesmar et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Presence of PSA-NCAM, as an embryonic form of NCAM, in the adult human brain was related to brain pathology, such as schizophrenia (Barbeau et al, 1995) and pituitary tumors (Trouillas et al, 2003). Of special interest is that PSA-NCAM has been implicated as an inhibitor of primary myelination in mice (Charles et al, 2000). Moreover, this molecule is re-expressed by demyelinated axons in human multiple sclerosis lesions (Charles et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Polysialic acid NCAM (PSA-NCAM) is a post-translationally-modified version of NCAM existing on both oligodendrocytes and axons [55][56][57][58] . Removal of PSA from axons [59] and oligodendrocytes [60] is a prerequisite for the initiation of myelination during development. in MS, PSA-NCAM is re-expressed on denuded axons in the plaque, and this could act as an inhibitor of remyelination and participate in disease progression [61] .…”
Section: Cell Adhesion Moleculesmentioning
confidence: 99%